2013
DOI: 10.1117/12.2019014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of specular highlights on 3D-2D face recognition

Abstract: One of the most popular form of biometrics is face recognition. Face recognition techniques typically assume that a face exhibits Lambertian reflectance. However, a face often exhibits prominent specularities, especially in outdoor environments. These specular highlights can compromise an identity authentication. In this work, we analyze the impact of such highlights on a 3D-2D face recognition system. First, we investigate three different specularity removal methods as preprocessing steps for face recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Unlike conventional works that propose specular prior on the spatial domain, this study is the first to utilize diffuse priors in the temporal domain. Leveraging the colors of surrounding pixels for hole-filling of highlight removal has already been studied in the non-deep-learning approach [6], [13]. The blur encoder was originally inspired by this conventional method.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike conventional works that propose specular prior on the spatial domain, this study is the first to utilize diffuse priors in the temporal domain. Leveraging the colors of surrounding pixels for hole-filling of highlight removal has already been studied in the non-deep-learning approach [6], [13]. The blur encoder was originally inspired by this conventional method.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…4, it is confirmed that the chromaticity of the saturated region is recovered with the blurred TDP. Reference [6] claims that Gaussian blurred prior can be a helpful cue for the reduction of saturation artifacts and noises in the image. These previous studies show that the surrounding pixels contribute to alleviating hole artifacts.…”
Section: A Temporal Dark Priormentioning
confidence: 99%
See 1 more Smart Citation
“…where each t i j is an entry of the 3x3 matrix T T T from (3), appeared also in (6). The cost function E( α R , α G , α B ) is regularized with a summation of L2 norms of α i -s in each color channel, primarily, to avoid overfitting.…”
Section: B Regularized Non-negative Least Squares (Rnnls)mentioning
confidence: 99%
“…Lighting can severely change the appearance of the human face and confound the information which is needed for reconstruction of the face model and face recognition [19] [22] [6]. Not only emitters but also surrounding objects, also from the off-screen space, influence the illumination; objects such as walls, ground, cloths, etc.…”
Section: Introductionmentioning
confidence: 99%